STUDI PEMANFAATAN KOTORAN TERNAK UNTUK PEMBANGKIT LISTRIK TENAGA BIOGAS DI BALI - Candra Santoso, Michael; Giriantari, I. A. D.; Ariastina, W. G. (Jurnal SPEKTRUM; Vol 6 No 4 (2019): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2019.v06.i04.p9, 2019)
In this journal, an analysis is carried out on the use of livestock manure for use as a biogas power plant in Bali Province. The purpose of this analysis is to find out how much potential electrical energy can be obtained from livestock manure to be developed into a biogas power plant in Bali Province. 8 types of livestock are used as analysis material including cattle, buffalo, goats, horses, sheep, pigs, chickens, and ducks. Livestock population data in Bali Province from 2013 to 2017 listed in the Livestock and Animal Health Statistics book obtained from the Directorate General of Animal Husbandry and Health (Ministry of Agriculture), is used as the base year of analysis to obtain the average value of the population level of each types of farm animals. The analysis of the total potential of electrical energy is done by calculating the total mass of manure per day, the percentage of dry matter content of each type of manure as well as the biogas that can be produced from each type of livestock according to the standards of the Ministry of Agriculture. The total potential of electrical energy can be obtained from the total amount of biogas produced, where 1 m3 of biogas can be converted into electrical energy of 4,7 kWh. Based on the results of the analysis conducted, the total biogas that can be produced is 246.130,81 m3 of biogas, or if it is converted into electrical energy equivalent to 1.156.814,81 kWh/day or around 1,16 GWh/day from the average total population livestock in Bali Province are 19.183.779 livestock.